‘Elastic band strategy’: women's lived experiences of coping with domestic violence in rural Indonesia - Elli Nur Hayati; Malin Eriksson; Mohammad Hakimi; Ulf Högberg; Maria Emmelin (Taylor & Francis Group, 2013)
Background: Experiencing domestic violence is considered a chronic and stressful life event. A theoretical framework of coping strategies can be used to understand how women deal with domestic violence. Traditional values strongly influenced by religious teachings that interpret men as the leaders of women play an important role in the lives of Javanese women, where women are obliged to obey their husbands. Little is known about how sociocultural and psychosocial contexts influence the ways in which women cope with domestic violence. Objective: Our study aimed to deepen our understanding of how rural Javanese women cope with domestic violence. Our objective was to explore how the sociocultural context influences coping dynamics of women survivors of domestic violence in rural Purworejo. Design: A phenomenological approach was used to transform lived experiences into textual expressions of the coping dynamics of women survivors of domestic violence. Results: Experiencing chronic violence ruined the women's personal lives because of the associated physical, mental, psychosocial, and financial impairments. These chronic stressors led women to access external and internal resources to form coping strategies. Both external and internal factors prompted conflicting impulses to seek support, that is, to escape versus remain in the relationship. This strong tension led to a coping strategy that implied a long-term process of moving between actively opposing the violence and surrendering or tolerating the situation, resembling an elastic band that stretches in and out. Conclusions: Women survivors in Purworejo face a lack of institutional support and tend to have traditional beliefs that hamper their potential to stop the abuse. Although the women in this study were educated and economically independent, they still had difficulty mobilizing internal and external support to end the abuse, partly due to internalized gender norms.